Chemical Linkers and Activation Mechanisms in Stimuli-Responsive Prodrug Design - Irfan, Hadiya; Alamgir, Lohar Fatama Qausar (American Journal of Biomedicine and Pharmacy, 2026)
Stimuli-responsive prodrug design has emerged as an advanced strategy to improve drug selectivity, therapeutic efficacy, and safety by enabling controlled activation of pharmacologically inactive compounds at specific target sites. Central to this approach is the rational selection of chemical linkers and activation mechanisms that respond to endogenous or exogenous stimuli such as pH variations, redox gradients, enzymatic activity, hypoxia, or external triggers like light and heat. Chemical linkers act as molecular switches that maintain prodrug stability during systemic circulation while ensuring efficient and predictable drug release at the desired site of action. This article provides a comprehensive analysis of the structural characteristics, cleavage behaviors, and biological performance of commonly used linkers in stimuli-responsive prodrugs. By integrating insights from medicinal chemistry, pharmacokinetics, and nanomedicine, this review highlights how linker chemistry and activation pathways directly influence drug release kinetics, targeting precision, and clinical potential, offering guidance for the rational development of next-generation prodrug systems. Stimuli-responsive prodrug systems represent an advanced paradigm in modern drug delivery, aiming to achieve precise control over therapeutic activation while minimizing off-target toxicity. Central to these systems is the incorporation of cleavable molecular connectors that regulate the transition from an inactive precursor to an active pharmaceutical agent under specific physiological or externally applied conditions. These connectors are engineered to remain intact during systemic circulation and to undergo selective transformation within pathological environments characterized by distinct biochemical or physicochemical features. Comprehensive evaluation of experimental evidence demonstrates that rationally engineered activation pathways significantly enhance tissue selectivity, improve pharmacokinetic behavior, and reduce systemic adverse effects. This analysis consolidates current understanding of how molecular architecture governs activation efficiency and therapeutic performance, emphasizing the critical role of controlled responsiveness in the development of next-generation precision medicines.